An Unusual Case of Double Heterotopic Pancreatic Tissues in the Same Localization - Kalkan, İsmail Hakkı; Öztaş, Erkin; Suvak, Burak; Yildiz, Hakan; Beyazit, Yavuz; Ibiş, Mehmet (JOP. Journal of the Pancreas, 2012)
No abstract available.